The intracellular bacterium Anaplasma phagocytophilum selectively manipulates the levels of vertebrate host proteins in the tick vector Ixodes scapularis - Villar, Margarita (Parasit Vectors, 2016)
BACKGROUND: The intracellular bacteria Anaplasma phagocytophilum are emerging zoonotic pathogens affecting human and animal health, and a good model for the study of tick-host-pathogen interactions. This tick-borne pathogen is transmitted by Ixodes scapularis in the United States where it causes human granulocytic anaplasmosis. Tick midguts and salivary glands play a major role during tick feeding and development, and in pathogen acquisition, multiplication and transmission. Vertebrate host proteins are found in tick midguts after feeding and have been described in the salivary glands of fed and unfed ticks, suggesting a role for these proteins during tick feeding and development. Furthermore, recent results suggested the hypothesis that pathogen infection affects tick metabolic processes to modify host protein digestion and persistence in the tick with possible implications for tick physiology and pathogen life-cycle. METHODS: To address this hypothesis, herein we used I. scapularis female ticks fed on uninfected and A. phagocytophilum-infected sheep to characterize host protein content in midguts and salivary glands by proteomic analysis of tick tissues. RESULTS: The results evidenced a clear difference in the host protein content between tick midguts and salivary glands in response to infection suggesting that A. phagocytophilum selectively manipulates the levels of vertebrate host proteins in ticks in a tissue-specific manner to facilitate pathogen infection, multiplication and transmission while preserving tick feeding and development. The mechanisms by which A. phagocytophilum manipulates the levels of vertebrate host proteins are not known, but the results obtained here suggested that it might include the modification of proteolytic pathways. CONCLUSIONS: The results of this study provided evidence to support that A. phagocytophilum affect tick proteolytic pathways to selectively manipulate the levels of vertebrate host proteins in a tissue-specific manner to increase tick vector capacity. Investigating the biological relevance of host proteins in tick biology and pathogen infection and the mechanisms used by A. phagocytophilum to manipulate host protein content is essential to advance our knowledge of tick-host-pathogen molecular interactions. These results have implications for the identification of new targets for the development of vaccines for the control of tick-borne diseases. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-016-1747-3) contains supplementary material, which is available to authorized users.